CABO FRIO - UM ENCLAVE SEMIÁRIDO NO LITORAL ÚMIDO DO ESTADO DO RIO DE JANEIRO: RESPOSTAS DO CLIMA ATUAL E DA VEGETAÇÃO PRETÉRITA - Coe, Heloisa Helena Gomes; Carvalho, Cacilda Nascimento de (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2013)
Located on the northeast coast of the State of Rio de Janeiro, Brazil, Cabo Frio region has been considered a phytogeographical enclave, with a drier climate than the rest of this coast, a redoubt for the “caatinga” like vegetation, dominated by xeromorphic forests, Cactaceae and Bromeliaceae. In order to contribute to this discussion in a singular way, this work makes multivariate analysis of similarity of variables of the current climate, comparing Cabo Frio with its more humid surroundings and the “caatinga” of Brazilian northeast. We also analyze possible changes in regional palaeovegetation, using phytoliths as proxy. We conclude that Cabo Frio has a climate more similar to the “caatinga” than to its surrounding, and that the vegetation, from 13,000 years cal BP, did not present major changes.